Syllabus Design for Computer Extracurricular Based on Internet of Things - Agata, Dias; Besari, Adnan Rachmad Anom; Wibowo, Iwan Kurnianto; Putri, Berliana Cahyaniati Purnomo (Beyond Words, 2018)
Abstract This study presents the process of designing a syllabus for computer extracurricular based on Internet of Things to be implemented in junior high schools in Indonesia. The process of designing the syllabus is based on the regulations of Indonesia Ministry of Education and Culture and adapted to Revised Bloom Taxonomy. There are six competency standards which is formulated in accordance to the junior high school curriculum and develop into six basic competencies for syllabus design. Six basic competencies are adapted to Internet of Things-based learning materials, then elaborated in indicators of competency achievement from Revised Bloom Taxonomy. The results show that all indicators mentioned in the syllabus are in accordance with the competency standards of junior high school students. In terms of the Knowledge dimension, the factual, conceptual, procedural and metacognitive points of knowledge have been fulfilled with the emergence of cognitive domain verb in each indicator of achievement of competence in the syllabus that has been designed. Various learning activities in the syllabus are comprehensively made so that students can perform practical work in accordance with the learning materials. Learning facilities in each section cover practicum teaching modules, power points, videos, practicum tool modules, and LCD projectors. The assessments for students include written tests, practicum and making products. Each assessment is adjusted to the basic competency and learning materials that have been formulated.